Response of Nitrogen and Potassium Fertigation to “Waris” Almond (Prunus dulcis) under Northwestern Himalayan Region of India - Dinesh Kumar; N. Ahmed (The Scientific World Journal)
A field experiment was conducted on almond (Prunus dulcis) to study the effect of N&K fertigation on growth, yields and leaf nutrient status over two seasons (2011 and 2012) in Srinagar, Jammu and Kashmir, India. There were six treatments, namely, T1—100% recommended dose of fertilizers as soil application, T2—100% RDF through fertigations, T3—75% RDF through fertigation, T4—75% RDF through fertigation (split application), T5—50% RDF through fertigation and T6—50% RDF through fertigation (split application) with three replications under randomized block design. The results indicated that the maximum tree height (3.21 m and 3.56 m), nut weight (2.73 g and 1.94 g), nut yield (2.41 kg/tree and 5.98 kg/tree; 2.67 t/ha and 6.64 t/ha), and leaf nutrient content (2.34 and 2.38% N; 0.14 and 0.17% P; 1.37 and 1.41% K) were recorded in T4 treatment, whereas the highest TCSA of main trunk, primary, secondary, and tertiary branches (72.67 and 90.28 cm2; 16.75 and 24.26 cm2; 3.83 and 7.49 cm2; 0.47 and 1.23 cm2), canopy volume (7.15 and 8.11 m3), and fruit number (990 and 3083/tree) were recorded in T2 in almond variety Waris.